Bacteria-Mediated Anomalous Rho GTPase Activation Alters Sperm Structure and Provokes Premature Capacitation Events: A Possible Mechanism of Infertility - Rivera, Bárbara (2025)
Male infertility is often linked to sperm quality issues; however, the mechanisms behind these alterations remain unclear in certain contexts. This study investigates the impact of anomalous Rho GTPase activation-a process triggered by bacterial toxins-on human sperm structure and function. Human spermatozoa were exposed in vitro to a Rho GTPase activator derived from Escherichia coli under both capacitating and non-capacitating conditions. The results showed increased RhoA GTPase activity in non-capacitating conditions, without affecting viability or mitochondrial membrane potential. However, progressive motility decreased across both conditions, while non-progressive motility and acrosome reaction rates increased. Additionally, intracellular calcium levels rose exclusively in non-capacitating conditions. Structural analysis revealed an increase in abnormal sperm morphology, particularly vacuoles in the sperm head. These findings highlight that anomalous Rho GTPase activation disrupts essential processes like motility and capacitation, which are crucial for successful fertilization. This study provides novel insights into how bacterial infections may induce sperm damage, proposing that Rho GTPase activity could serve as a biomarker for evaluating sperm quality in cases of infertility linked to urogenital infections. Understanding these mechanisms may improve diagnostic and therapeutic approaches for male infertility associated with bacterial pathogens. Human spermatozoa were exposed in vitro to a Rho GTPase activator derived from Escherichia coli under both capacitating and non-capacitating conditions.